P3.371 Reduction in HPV Prevalence Among Young Women Following Introduction of HPV Vaccine in the United States and Estimated Vaccine Effectiveness. (13th July 2013) - Markowitz, L E; Hariri, S; Lin, C; Dunne, E; Steinau, M; McQuillan, G; Unger, E R
Abstract : Background: Human papillomavirus (HPV) vaccination was introduced into the adolescent immunisation schedule in the United States in mid 2006. Vaccination is recommended for females at age 11 or 12 years and through age 26 if not previously vaccinated. Estimated 3-dose coverage was 32% among 13–17 year-olds in 2010. Objectives: To compare HPV prevalence among females in the first 4 years of the vaccine era (2007–2010) with the prevaccine era (2003–2006), and to determine vaccine effectiveness (VE). Methods: The National Health and Nutrition Examination Surveys (NHANES) are a series of cross sectional surveys, designed to be nationally representative of the civilian, non-institutionalised US population. HPV prevalence was determined in self-collected cervicovaginal swabs from females aged 14–59 years; 4150 in 2003–2006 and 4253 in 2007–2010. Type-specific HPV prevalence was determined by the Linear Array HPV Genotyping Assay. VE was estimated among sexually active 14–26 year-olds in 2007–2010. Results: Among females aged 14–19 years, vaccine type (VT) HPV prevalence decreased from 11.5% (95% CI = 9.2, 14.4) in 2003–2006 to 5.1% (95% CI = 3.8, 6.6) in 2007–2010; a 56% (95% CI = 37%, 69%) decline. Prevalence did not differ between the two time periods in other age groups. History of vaccination was associated with lower VT HPV prevalence among sexually active 14–19 years-olds, 3.5% vs. 12.6% (aRR = 0.18; 95% CI, 0.7–0.48, estimated VE = 82%) and among 20–26 year-olds, 12.4% vs 21.3% (aRR = 0.46; 95% CI, 0.22–0.99, estimated VE = 54%). Our sample size was too small to evaluate effectiveness by number of doses. Conclusions: Within 4 years of vaccine introduction, there was a decrease in VT HPV prevalence in a nationally representative sample of females aged 14–19 years. As expected, VE was lower among those vaccinated at older ages. Ongoing monitoring will allow assessment of vaccine impact on prevalence, possible cross protection or type replacement.